The Policy of Bener Meriah Regency Government Model Initiation in Evaluating the Use of Village Development Funds - Salawati; Praptining Sukowati; Sri Hartini Djatmikowati (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2020)
Initiation is the policy of the Bener Meriah Regency Government to evaluate the use of funds in development at the village level so that the use of funds is more targeted. Considering the existence of the village as a government organization has certain authority to manage and regulate the residents in this matter, the village is at the forefront in achieving development success, it is necessary to have an evaluation to lead to improvement. The initiation policy in evaluating as a model or new breakthrough by the District Government of Bener Meriah how to give appreciation in the form of additional funding for villages that can manage the budget on time, on quality and on target. To implement the policy model, a legal umbrella has been prepared in the form of a Perbub. The research objective is to describe and analyze the initiation policy model of the Bener Meriah Regency Government in evaluating the use of village development funds and To find out and analyze the initiation policy model strategy carried out by the Bener Meriah Regency Government in evaluating the use of village development funds. The method is a procedure carried out to find out something using systematic steps, so in this study the researcher used a descriptive qualitative method to describe the initiation policy model in evaluating the use of village development funds. Determination of informants was carried out by purposive sampling, while data collection techniques through observation and interview. The results showed that the policy model of the initiation of the Bener Meriah Regency Government in evaluating the use of village development funds as a new breakthrough was born because it was based on the improper use of funds amidst the abundance of the budget given by the government. The initiation policy model strategy undertaken by the Bener Meriah Regency Government in evaluating the use of village development funds through musrembang which then enters the implementation stage through the link between the results of the development planning and implementation becomes an evaluation of the use of funds.